The Growth of Staphylococcus aureus in the blood agar plate media of sheep blood and human blood groups A, B, AB, and O - Turista, Dora Dayu Rahma; Puspitasari, Eka (POLTEKKES KEMENKES YOGYAKARTA, 2019)
BAP media is a medium used to distinguish pathogenic bacteria based on their hemolytic power on red blood cells. Staphyllococcus aureus is a bacterium that is able to emolate red blood cells with 3 types of hemolysis, namely Î±, Î², Î³, and Î´. Usually BAP media is made by adding 5-10% sheep blood. Making BAP media using sheep blood has become a problem for several laboratories today, including health education laboratories. This is because the health education laboratory does not yet have a sheep farm, so it has not been able to procure sheep blood. The use of human blood as a substitute for sheep blood in making BAP media may be a solution, but it is not yet known whether there are differences in the growth and hemolysis of S. aureus bacteria on BAP media in sheep's blood and human blood. This research is an experimental study with a completely randomized design (CRD) of 3 replications which aims to determine whether there are differences in growth and hemolysis of bacteria S. aureus in BAP media of sheep blood and human blood groups A, B, AB, and O. The results showed that S. aureus bacteria could grow and show hemolysis in BAP media in sheep blood and human blood in groups A, B, AB, and O. The results of subsequent studies analyzed ANOVA using the software spss for windows with a significant level of 0.05. From the results of research and data analysis it can be concluded that S. aureus bacteria can grow and show hemolysis in BAP media of sheep blood and human blood groups A, B, AB and O, but there are significant differences in the number of S. aureus bacteria colonies grown in BAP media of sheep's blood and human blood groups A, B, AB and O.